The Role of Parents' and Teachers' Responsibilities for Children's Education from an Islamic Perspective - Ubaidillah, Ubaidillah; Purnawati, Putri; Najibah, Ainun; Hana, Hana (International Education Trend Issues, 2024)
Education is a human right, especially for children. If ignored, there will be chaos in all aspects of life because of ignorance. In this article, we discuss the educational responsibilities of children, these responsibilities are "photographed" from an Islamic perspective. This responsibility, if fulfilled, must have a clear foundation and must be strongly supported by pillars. Obtaining Islamic education is the right and obligation of all Muslims. The foundation is Islamic Aqidah and the first organizer is the family, namely parents, the main organizer is the government which is operationally implemented by the school. There must be teachers who are competent and have an Islamic personality. The community becomes a supporting organizer, so that the government's burden is lighter and education services are more evenly distributed. Family, school, community and government work synergistically. Help each other, strengthen and compete in advancing education. So that the goal of Islamic education can be realized, namely to produce people who are faithful, devout and have mastery of science and technology. In other words, it produces people with character, namely good people, people who have good hearts, good thoughts, and do good deeds.